Development of educational videos about bathing in bed newborns admitted to a neonatal unit - Maria Paula Custódio Silva; Cinthia Lorena Silva Barbosa Teixeira; Juliana da Silva Garcia Nascimento; Kleiton Gonçalves do Nascimento; Rui Carlos Negrão Baptista; Luciana Mara Monti Fonseca; Divanice Contim (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to develop and analyze evidence of content validity of educational videos about bathing newborns in bed in a neonatal unit. Method: applied and methodological research, carried out from December/2020 to February/2022, in three phases: pre-production, production, post-production. Validity was carried out by nurses specializing in social communication and nursing professionals, including the Brazilian Sign Language and assessment by nursing students. The Content Validity Index and Cronbach's alpha above 0.8 were considered for analysis. Results: the videos were entitled "Best practices: bathing newborns in the heated crib" and "Best practices: bathing newborns in the incubator", lasting seven minutes each, divided into six scenes that demonstrated the approach to parents, environment and material organization, preparing newborns, bathing and after-bath care. Conclusion: the videos will support permanent education processes, academic training and professional training in nursing.